Use of virtual reality to improve the representation, details and sensation of realistics scenarios in a Smart City - Ochoa, Carlos Alberto (Documenta Universitaria, Girona, 2019)
Abstract: Environments created with Microworlds are almost static and lifeless. One way to combat this problem is to associate the “Environment” with autonomous agents that allow the members of a herd, flock or flock to project vital characteristics. This article discusses the incorporation of animals into appropriate environments, as well as the definition of appropriate behaviors that enrich the experience. We propose an innovative model using Virtual Reality to improve a compare two scenarios one in Juarez City and another in Kotor, a city of Montenegro.